Brand Equity in University: Literature Review - Warganegara, Tri Lestira Putri; Suhaimi, Suhaimi; UmpuSinga, Hasrun Afandi; Barusman, M Yusuf S; Barusman, Andala Rama Putra; Habiburrahman, Habiburrahman (Penerbit Goodwood, 2024)
Purpose: A review of the history of university brand equity research is attempted to be given in this paper. Research methodology: Extracts from the Scopus database. Ten publications discussing university brand equity made up the sample, which spanned the years 2000 to 2203. The analysis approach groups articles according to pertinent subjects about institution brand equity. Results: All things considered, the study findings revealed that little study has been done on university brand equity. Limitations: Our research focuses exclusively on scientific articles published in the last 23 years and in the Scopus index. Contribution: Given the dearth of study on brand equity in the service industry, particularly in universities, this could offer researchers a chance to focus on university brand equity, particularly in Indonesia.